P096 Store-Operated Calcium Entry Controls Innate and Adaptive Immune Cell Function in Inflammatory Bowel Disease. (21st January 2022) - Letizia, M; Kaufmann, U; Wang, Y H; Gerbeth, L; Sand, A; Brunkhorst, M; Böttcher, C; Schlickeiser, S; Fernández-Zapata, C; Kunkel, D; Siegmund, B; Feske, S; et al.
Abstract: Background: Inflammatory bowel disease (IBD) represents a major clinical challenge in need of new treatment modalities to improve patient care. Store-operated calcium entry (SOCE) is the predominant calcium influx pathway in T cells, regulating many of their functional properties. However, it is currently unknown whether the pharmacologic inhibition of SOCE is a suitable drug target in IBD. Therefore, we aimed to investigate the effects of SOCE inhibitors (SOCEi) on lymphocytes and epithelial cells isolated from IBD patients. Methods: Peripheral blood mononuclear cells (PBMC), lamina propria lymphocytes (LPMCs) and epithelial cells were isolated from IBD patients undergoing colon resection. LPMCs or PBMCs were ex-vivo stimulated with Ionomycin/PMA ± SOCEi and subsequently stained with a panel of 37 immunological markers for mass cytometry acquisition. Ca2+ influx measurements were performed in order to assess the metabolic status of immune (PBMCs and LPMCs) and epithelial cells after SOCE blockade. Finally, murine models of colitis were used in order to investigate the effects of SOCE blockade on the induction of intestinal inflammation in-vivo . Results: Data on B, T, NK, and myeloid cells revealed that treatment with SOCEi caused a dose-dependent inhibition of Ca 2+ signaling in human gut-resident lymphocytes and PBMCs. The inhibition of SOCE attenuated the production of pathogenic cytokines including IL-2, IL-4, IL-6, IL-17, TNF-α and IFNγ by colonic T cells and ILCs, reduced the activation of B cells and the production of IL-6 by myeloid cells, without affecting the viability of primary human epithelial cells. Remarkably, mouse models of transfer colitis, in which SOCE signaling components have been blocked, revealed that SOCE is required for the induction of intestinal inflammation in-vivo . Conclusion: Our data revealed for the first time that the cytokine production and the activation of several immune cell subtypes can be modulated by SOCE blockade in human intestinal inflammation, identifying SOCE as a novel therapeutic target in colitis.